Improvement of neuronal differentiation by carbon monoxide - Almeida, Ana S. (2018)
This work was supported by the Portuguese Fundação para a Ciência e Tecnologia (FCT) grant FCT-ANR/NEU-NMC/0022/2012, FCT grant UID/Multi/04462/2013, I&D 2015-2020 iNOVA4Health - Programme in Translacional Medicine COST Action BM1005 “European Network on Gasotransmitters”, HLAV's FCT support IF/00185/2012, ASA's SFRH/BD/78440/2011 and NLS's PD/BD/127819/2016 fellowships.